The violences of settler colonialism and the maintenance of the heteropatriarchal social order - Maddison, Sarah (Interconnecting the violences of men, 2025)
Colonisation is inherently and inevitably violent. It is not possible to invade and occupy another’s territory without violence. Violence is in the DNA of dispossession and all the atrocity that entails. Violence, too, sustains the settler colony. As Patrick Wolfe famously argued, “invasion is a structure not an event”; the violence of invasion is structured into contemporary settler colonial societies, perpetuating their heteropatriarchal and racialised social orders through violences that seek to repress, contain, and eliminate those who challenge the legitimacy of the status quo. Colonial violences, then, are not only historical but also contemporary, multiple, gendered, and relentless. Indigenous feminist scholars have pointed to the connections between colonialism and the violences that sustain the heteropatriarchal social order in settler colonial societies. This chapter connects these intersecting, overlapping violences of colonialism from invasion through to the present day, across historical periods of invasion, frontier warfare, dispossession, sexual exploitation, child removal, and assimilation into present-day practices of carceral violence, hyper-policing, and surveillance. Focusing on the settler colonial experience, the chapter draws out the continuities in violence from invasion to the present day, arguing that all colonial violence serves the aim of maintaining and advancing a racialised, heteropatriarchal, and colonial social order.